Refleksi Kritis Terhadap Program JPS Jaring Pengaman Sosial Studi Kasus Proyek PDM-DKE - M Baiquni (JKAP (Jurnal Kebijakan dan Administrasi Publik), 1999)
This essay is a critical reflection on the implementation of faring Pengaman Sosial (Social Safety Net) programme introduced by the Government of Indonesia. There are two level of analysis focused on this essay. First, the author analyses the paradigm used in understanding poverty issues which is in turn reflected in the government-supported poverty reduction policy. Second, analysis is focused on the case study of field experience in Ponorogo District. So far, the program has come to two different impacts. On the one hand, the program has positive impacts in terms of empowerment of the community and improvement of the government official openess. On the other hand, there are several weaknesses that were not anticipated yet such as social jealousy, social solidarity threats and gender bias.